2014
DOI: 10.1111/ele.12351
|View full text |Cite
|
Sign up to set email alerts
|

External morphology explains the success of biological invasions

Abstract: Biological invasions have become major players in the current biodiversity crisis, but realistic tools to predict which species will establish successful populations are still unavailable. Here we present a novel approach that requires only a morphometric characterisation of the species. Using fish invasions of the Mediterranean, we show that the abundance of non-indigenous fishes correlates with the location and relative size of occupied morphological space within the receiving pool of species. Those invaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 44 publications
3
118
0
Order By: Relevance
“…Third, the ecomorphological paradigm assumes that clusters of specimens or species within morphological spaces represent functional groups (Thuiller et al 2010;Azzurro et al 2014). Although some aspects of fish morphology provide reasonable surrogates for components of ecological performance, and Toussaint et al's (2016) finding for highest FD in the tropics is consistent with prior research (e.g.…”
supporting
confidence: 75%
“…Third, the ecomorphological paradigm assumes that clusters of specimens or species within morphological spaces represent functional groups (Thuiller et al 2010;Azzurro et al 2014). Although some aspects of fish morphology provide reasonable surrogates for components of ecological performance, and Toussaint et al's (2016) finding for highest FD in the tropics is consistent with prior research (e.g.…”
supporting
confidence: 75%
“…Overall, the morphological positions of vagrant species were strongly skewed to the upper and lower left-hand corners of the convex hull. Azzuro et al [13] also found that species belonging to the family Chaetodontidae had a high invasion probability in the Mediterranean, but argued that habitat constraints (obligate association with coral of the species concerned) not accounted for in the methodology meant that they would remain rare. The butterflyfishes identified by our study as having strong range-shift potential actually show versatility in their habitat associations, even within reef environments.…”
Section: Resultsmentioning
confidence: 99%
“…A database of 110 species of bony fishes was compiled (electronic supplementary material, table S1) and an image of each species (left-hand side of adult individual) was sourced from online resources. Species' morphology was then characterized using 27 anatomical landmarks with ecological significance (following [13,16,17]; electronic supplementary material, table S1). Landmarking of images was done using tpsDig v. 1.40 [18], and scaled via a generalized least-squares procedure (generalized Procrustes) to eliminate the effect of isometric body-size variation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B, morphospace 2) (Young et al 2009, Friedman 2010; and third, a partial combination of the first two methods, including the shape, size and position of all fins and sensorial organs (Fig. 1C, morphospace 3) (Recasens et al 2006, Farré et al 2013, Azzurro et al 2014. We digitized the landmarks and semilandmarks in one standardized image of the left profile of species previously obtained as a consensus figure from different specimens using tpsDig v. 2.16 software (Rohlf 2003a) for geometric morphometric analysis.…”
Section: Building Morphospacesmentioning
confidence: 99%